Calcium homeostasis in aging neurons - Nikoletopoulou, Vassiliki; Tavernarakis, Nektarios (Frontiers in Genetics, 2012)
The nervous system becomes increasingly vulnerable to insults and prone to dysfunction during aging. Age-related decline of neuronal function is manifested by the late onset of many neurodegenerative disorders, as well as by reduced signaling and processing capacity of individual neuron populations. Recent findings indicate that impairment of Ca2+ homeostasis underlies the increased susceptibility of neurons to damage, associated with the aging process. However, the impact of aging on Ca2+ homeostasis in neurons remains largely unknown. Here, we survey the molecular mechanisms that mediate neuronal Ca2+ homeostasis and discuss the impact of aging on their efficacy. To address the question of how aging impinges on Ca2+ homeostasis, we consider potential nodes through which mechanisms regulating Ca2+ levels interface with molecular pathways known to influence the process of aging and senescent decline. Delineation of this crosstalk would facilitate the development of interventions aiming to fortify neurons against age-associated functional deterioration and death by augmenting Ca2+ homeostasis.